Perancangan Sistem Informasi Pengarsipan Surat Masuk dan Surat Keluar pada Instansi Balitbangda Provinsi Sumatera Selatan - Pramu Dita, Dito; Rahayu, Sri (Universitas Multi Data Palembang, 2024)
Archives are needed to carry out administrative processes in every company, having long, medium and short term goals and objectives to be achieved. Every possible effort is made to archieve this goal. One of them play a very important role in the company’s progress, namely a good filling system for proper and correct file management. A good file storage system can help make tasks easier and support the success of future business goals. The south Sumatera Province Regional Research and Development Agency still uses manual methods so that delays and errors often occur in recording incoming and outgoing letters. The method used in this research is the waterfall method, which is a method that is useful for the software development process. This waterfall method is developed systematically from one stage to the next. The results of the research procedurally obtained data on incoming letters, outgoing letters, letter diaries, and displayed reports that would be needed to make it easier for the South Sumatra Province Balitbangda to process information on incoming and outgoing letters. At the stage of manually filing incoming and outgoing letters, it has been replaced with an electronic filing system. All Balitbangda of South Sumatra Province can access the letter archiving information system, the letter files entered can be immediately archived and edited. Users can also add and change passwords.